2018
DOI: 10.5489/cuaj.5548
|View full text |Cite
|
Sign up to set email alerts
|

Opportunities for augmentation cystoplasty revision without additional bowel harvest: “Hourglass” deformity or non-detubularized augment

Abstract: Introduction: We describe our experience performing bladder augmentation revision without additional bowel harvest for certain suboptimal cystoplasty configurations. Methods: We identified patients with prior bladder augmentation who underwent augmentation revision without additional bowel harvest at our institution. These patients were identified to have either “hourglass” deformity or non-detubularized augment previously. Revision was performed using an open technique by detaching the prior augment and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…If the initial cystotomy is too small, the anastomosis may narrow, resulting in an 'hourglass deformity'. 1 There are few studies on sequelae and management of hour-glass deformity postaugmentation. The largest is a case series of seven patients who underwent removal of the ileal augment, enlargement of the cystotomy, and re-anastomosis of the ileal patch.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…If the initial cystotomy is too small, the anastomosis may narrow, resulting in an 'hourglass deformity'. 1 There are few studies on sequelae and management of hour-glass deformity postaugmentation. The largest is a case series of seven patients who underwent removal of the ileal augment, enlargement of the cystotomy, and re-anastomosis of the ileal patch.…”
Section: Discussionmentioning
confidence: 99%
“…Post-operative follow-up demonstrated resolution of the hour-glass deformity and improvement in voiding pressures. 1 A study on need for re-augmentation in patients with bladder exstrophy found the formation of an hour-glass deformity to be an indication for re-augmentation in 1 out of 17 patients. 2 Patients with bladder exstrophy are challenging given their small native bladder making enlargement of the original cystotomy difficult.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation